Introduction to physical education, fitness, and sport - Siedentop, Daryl Professor Emeritus; Van der Mars, Hans 1955- (Champaign, IL Human Kinetics, Inc., 2023)
"The ninth edition of Introduction to Physical Education, Fitness, and Sport is as robust and instrumental as ever for students preparing for careers in the various physical activity fields. And the latest version of this long-running and seminal text is chock-full of new material for budding teachers, coaches, fitness professionals, recreation leaders, and program leaders.This book covers a broad spectrum of careers and professions, including those in physical education, health, dance, fitness, sport, recreation, athletic training, and athletic administration. The authors provide an overview of the respective professions and offer a deep dive into individual careers. In addition, the text explores the role of public policy across local, state, and federal levels, noting how various physical activity professions are affected by regulations.New content in this edition includes the following:Five new chapters cover dance education, recreational leadership, health education, contemporary physical education curriculum models, and exemplary physical education programs.Updated content on how economic, racial, and ethnic disparities affect physical activity and physical activity professions will help students anticipate real-life issues.New evidence, data, and information throughout the text will help students understand the issues, problems, and programmatic solutions in the various fields as they prepare to meet and solve those problems.The expanded and updated physical education chapters reflect current trends and developments.The new chapters on dance education, recreational leadership, and health education broaden the book's scope as they show the role these allied physical activity professions play in the larger efforts to promote and support physical activity as a way to create a healthy citizenry.All chapters throughout the text have been updated to reflect the most current information on the topics. And the book's web-based ancillaries, which include a range of instructor tools, have also been revised and expanded.Introduction to Physical Education, Fitness, and Sport is organized into six parts:Part I provides a thorough understanding of the health issues related to physical inactivity and of the evolution of physical activity programs.Parts II, III, and IV focus on concepts, programs, professions, and barriers to overcome in physical education, fitness, and sport, respectively.Part V delves into the allied physical activity professions of dance and dance education, recreation, and health education, exploring the concepts, professions, and issues in each area.Part VI tackles the subdisciplines of kinesiology that support physical activity, such as exercise physiology, sport pedagogy, sport and exercise psychology, sport philosophy, biomechanics, and more.Introduction to Physical Education, Fitness, and Sport will help students make more informed career choices, understand the professional issues they will face, and be in a better position to develop high-quality programs and make those programs widely available.Ultimately, this book will help new generations of physical activity professionals provide positive solutions to the problems that exist in their fields and to make lifelong impacts on their students"--
Machine generated contents note: Part I. The Current Context and Evolution of Physical Activity -- Chapter 1. The Dilemma of Our Times: Life Span Physical Activity and the Obesity Health Crisis -- Trends in Sugary Drink and Fast Food Consumption -- Federal and State Legislation to Address Childhood Nutrition and Wellness -- The Costs of Overweight and Obesity -- National Goals for Physical Activity in Schools and Beyond -- The National Physical Activity Plan -- Grading Progress on Physical Activity -- Summary -- Discussion Questions -- Chapter 2. Life Span Physical Activity: A Revolution Not Limited by Age or Gender -- The Early Years -- Youth: The Transition Years -- Young Adulthood -- Older Adulthood -- The New Settings for Physical Activity -- The Emerging Characteristics of Life Span Physical Activity -- Confronting Major Issues -- Summary -- Discussion Questions -- Chapter 3. The Evolution of Physical Activity Philosophies and Programs -- Gymnastics Philosophies and Systems: The Beginning of Physical Education in America -- The Emergence of Physical Activity in American Physical Education -- The Emergence of Fitness -- The Emergence of Organized Sport in America -- Sport on College Campuses -- Sport During the Depression, World War II, and Beyond -- Philosophical Influences in American Physical Education, Fitness, and Sport -- The Emergence of Physical Activity for Girls and Women -- Recent Philosophical Influences on Physical Activity -- Summary -- Discussion Questions -- Chapter 4. Developing an Infrastructure to Support Physical Activity and Healthy Lifestyles -- Physical Fitness and Physical Activity: Whose Responsibility? -- National-Level Efforts to Support Physical Activity Infrastructures -- State-Level Efforts to Support Physical Activity Infrastructures -- Local Efforts to Support Physical Activity Infrastructures -- Allied Fields Supporting Physical Activity Infrastructure -- Six Crucial Themes Defining Our Present and Future -- Summary -- Discussion Questions -- Part II. Physical Education -- Chapter 5. Basic Concepts of Physical Education -- 20th-Century Philosophical Influences on Physical Education -- National Physical Education Goals and Content Standards -- What Is the Subject Matter of Physical Education? -- Physical Education and Physical Activity: The Same or Different? -- Inclusion of Students With Disabilities in Physical Education -- Summary -- Discussion Questions -- Chapter 6. Contemporary Curriculum and Instruction Models -- The Skill Themes Model -- Health-Optimizing Physical Education -- Conceptual Physical Education -- Teaching Personal and Social Responsibility -- Sport Education -- Games-Based Models for Teaching Sport Games -- Adventure Education -- The Eclectic Curriculum -- Summary -- Discussion Questions -- Chapter 7. The Physical Education Profession -- The Physical Education Teacher -- Preparing to Become a Physical Education Teacher -- Physical Education Teachers as Campus-Level Physical Activity Leaders -- Technology in Physical Education -- Summary -- Discussion Questions -- Chapter 8. Exemplary Physical Education Programs -- The Active and Healthy Schools Program -- A High School Program That Individualizes Students' Activity Experiences -- A Rural School's Effort to Maximize Campus-Based Physical Activity Beyond Physical Education -- A High-School Program Blending Health and Wellness, Outdoor Pursuits, and Sport -- A Districtwide Healthy Lifestyles Curriculum -- A Middle School With a Strong Focus on Learning Personal and Social Responsibility Skills -- A High School Program With an Outdoor Pursuits Option -- A Research-Based National Elementary School Program -- A District-Level Initiative Linking Physical Education With the Community -- A High School Program With Sport Education as the Central Focus -- A High School Physical Education Program With Proficiency Expectations -- What Makes These Programs Work? -- A State Approach to Revitalizing High School Physical Education -- Building a Vision for the Future -- Rethinking Secondary School Physical Education -- Legislative Efforts to Support Physical Education -- Quality Physical Education Programs-Moving Forward -- Summary -- Discussion Questions -- Chapter 9. The Future of Physical Education: Problems and Barriers to Overcome -- Improving Physical Education Through Establishing Strong State-Level Legislation -- Consequences of Weak or Nonexistent State-Level Policies -- General Problems in Physical Education -- Issues in Elementary School Physical Education -- Issues in Secondary School Physical Education -- The Future of Physical Education in a Sport and Fitness Culture -- Becoming Architects of a Thriving Physical Education Profession -- Summary -- Discussion Questions -- Part III. Fitness -- Chapter 10. Basic Concepts of Fitness and Physical Activity -- Understanding Fitness and Physical Activity -- Cosmetic Fitness -- The Dose-Response Debate -- The FITT Formula -- The Social Gradient in Health and Fitness -- Fitness-Training Concepts and Principles -- The Measurement of Fitness and Physical Activity -- Summary -- Discussion Questions -- Chapter 11. Fitness and Physical Activity Programs and Professions -- Fitness Levels Among Children and Adolescents -- Physical Activity Patterns Among Children and Adolescents -- Adult Fitness Levels and Activity Patterns -- Fitness and Activity Patterns Among Older Adults -- Fitness and Physical Activity for People With Disabilities -- Worksite Fitness and Wellness Programs -- National Efforts to Promote Fitness and Physical Activity -- Legislative Efforts to Improve Child and Youth Fitness -- Physical Fitness Instruction: By Whom? -- Summary -- Discussion Questions -- Chapter 12. Problems and Barriers to Overcome in Fitness -- The Complexity of Dealing With the Obesity Epidemic -- The Costs of Inadequate Health-Related Fitness -- Precipitating Factors Related to Overweight and Obesity -- Developing Self-Efficacy for Physical Activity -- Developing a Fitness-Educated Public -- Persistent Inequity Issues in Fitness and Activity -- Certification of Fitness Leaders -- Fitness Issues in Physical Education -- Fitness and Aging: Changing Views and Expectations -- Summary -- Discussion Questions -- Part IV. Sport -- Chapter 13. Basic Concepts of Sport -- Sport: The Natural Religion -- Leisure, Play, Games, and Competition -- The Institutionalization of Sport -- Sport Spectating -- Sport Aesthetics -- Sport Ethics -- The Developmental Potential of Sport -- Inequities in Sport -- Summary -- Discussion Questions -- Chapter 14. Sport Programs and Professions -- Child and Youth Sport -- Interscholastic Sport -- Collegiate Sport Programs -- Professional Sport -- Organized Recreational Sport -- Sport for People With Disabilities -- Masters or Veterans Sport -- Nonparticipant Sport Involvement -- Sports Medicine and Athletic Training -- Sport and Technology -- Summary -- Discussion Questions -- Chapter 15. Problems and Barriers to Overcome in Sport -- Child and Youth Sport -- Interscholastic Sport -- Intercollegiate Sport -- Sport Systems -- Summary -- Discussion Questions -- Part V. The Allied Physical Activity Professions -- Chapter 16. Dance and Dance Education: Concepts, Professions, and Issues -- Gayle Kassing, PhD -- Defining Dance and Dance Education -- Dance Forms and Genres -- Dance Content Knowledge -- Teaching Dance in the 21st Century -- Sectors of Dance Education and Overarching Issues -- Future Directions for Dance Education in the 21st Century -- Summary -- Discussion Questions -- Chapter 17. Recreation: Concepts, Professions, and Issues -- Eric Legg -- Community Parks and Recreation -- Key Concepts -- History of Leisure, Recreation, and Play -- Recreation Providers Today -- Recreation Spaces and Programs -- Current Trends and Issues in Recreation -- Summary -- Discussion Questions -- Chapter 18. Health Education: Concepts, Professions, and Issues -- Sarah Benes, EdD, MPH, CHES, and Holly Alperin, EdM, MCHES -- Health Education Defined -- The Need for Health Education -- Benefits of Health Education -- Components and Principles of Effective Health Education -- Skills for Health Education Teachers -- Current Barriers and Issues -- Conclusion -- Summary -- Discussion Questions -- Part VI. Kinesiology: The Scientific Foundation of Human Movement -- Chapter 19. The Subdisciplines of Kinesiology That Support Physical Activity Professions -- Exercise Physiology -- Biomechanics -- Motor Behavior -- Sport and Exercise Psychology -- Sport Pedagogy -- Sport Sociology -- Sport Humanities Subdisciplines -- Summary -- Discussion Questions
Includes bibliographical references and index
Keywords: Physical education and training; Physical fitness; Sports sciences; Sports